A carbon-based azide film suitable for MEMS micro-charge and a preparation method thereof
The preparation of carbon-based azide films through electrospinning and hot pressing technology has solved the problem of high sensitivity and unstableness of existing azide-type detonating agents, and achieved moderate sensitivity film preparation, suitable for MEMS micro-charges .
Patent Information
- Application Number
- CN202310141726.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-02-17
AI Technical Summary
The existing azide-type detonating agents have a high sensitivity and are mostly powder-like, which is difficult to be compatible with the MEMS process and are unstable.
Carbon-based azide films were prepared by electrospinning technology, and carbon frame films with uniformly loaded metal particles were quickly obtained through hot pressing technology, followed by in-situ azide to prepare carbon-based films suitable for MEMS micro-charges. Azide film.
It realizes the rapid preparation of a carbon-based azide film with moderate sensitivity. The film is easy to process and mold, compatible with the MEMS process, and is suitable for MEMS micro-charge.
Smart Images

Figure CN116288935B_ABST
Abstract
Description
[0001] Technical field: The present invention belongs to the technical field of energetic materials, and relates to a carbon-based azide film suitable for MEMS micro-charges and a preparation method thereof. Background Art
[0002] As weapon systems develop towards intelligence, miniaturization and integration, the fourth generation of new concept pyrotechnics has emerged. Compared with traditional pyrotechnics, the fourth generation of pyrotechnics usually include energy response and transmission at a microscale. Compared with the traditional pressing and casting charging methods, their manufacturing methods mostly use in-situ charging methods that are compatible with MEMS technology.
[0003] In-situ charging is usually done on the surface of a microstructure transducer or a silicon-based charge cavity, using technologies compatible with MEMS technology, such as in-situ precipitation and in-situ synthesis, to directly react and generate the required micro-nano agents at the designated charging position. This method can not only effectively reduce the risk of charging, but also meet the needs of the fourth-generation pyrotechnics for microscale charging. At present, this in-situ charging technology is mostly used to prepare detonating agents that are very sensitive to external stimuli, such as lead azide, copper azide, silver azide and other azide detonators. However, the above-mentioned agents have high sensitivity and are mostly in powder form. The agent system is easy to disperse and unstable. Some researchers have reduced their sensitivity by adding carbon materials with excellent electrical and thermal conductivity, or by preparing porous copper and carbon skeletons through a high-temperature calcination process, but the samples are still in powder form, which is not easy to charge safely and is not easy to achieve mutual compatibility with MEMS technology.
[0004] Electrospinning technology has the advantages of simple operation and low cost. It can realize mass production. The prepared thin film materials are easy to functionalize and post-process. It is compatible with MEMS technology. Electrospinning technology can be used to prepare thin film agents for micro-charging. Hot pressing technology refers to the use of specific temperature and a certain pressure in a short time to quickly shape the sample. Compared with the traditional high-temperature calcination process, it is more efficient and can be quickly formed in a short time. The prepared materials can still maintain good film properties and are easy to process and functionalize in the later stage. It can realize the rapid preparation of carbon skeleton films. Therefore, electrospinning technology can be combined with hot pressing technology to design and prepare carbon-based thin film azide agents with moderate sensitivity and suitable for MEMS micro-charging process. Summary of the invention
[0005] The purpose of the present invention is to provide a carbon-based azide film suitable for MEMS micro-charge and a rapid preparation method thereof. Compared with traditional azides and azides modified by carbon materials, the material is in the form of a film and is easy to be cut and processed into shape. It also has good sensitivity characteristics and is suitable for MEMS micro-charge.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a carbon-based azide film with better sensitivity performance, which is prepared by electrospinning technology, and a carbon skeleton film uniformly loaded with metal particles is quickly obtained by hot pressing technology, and a carbon-based azide film suitable for MEMS micro-charge is obtained by subsequent in-situ azidation.
[0007] The specific steps of the method for preparing the azide film suitable for MEMS micro-charge are as follows:
[0008] Step 1: Place a certain concentration of spinnable polymer materials and metal salts in an organic solvent at a certain mass ratio, stir for a period of time at a certain temperature, and after they are completely dissolved, place the solution in a syringe with a nozzle, and use an electrospinning instrument to spin at a certain voltage and injection rate. After spinning, peel off the prepared film and place it in a 50°C oven to dry.
[0009] Step 2: Place the film in step 1 in a polytetrafluoroethylene mold and evenly cover its surface with aluminum foil. Use a handheld hot press to quickly heat press it at a specific temperature for a certain period of time, and then obtain a carbon-based film after the temperature returns to room temperature.
[0010] Step 3: Place sodium azide and stearic acid in a gas generator, and place the carbon-based film obtained in step 2 in a one-way ventilation tube. The hydrazoic acid gas generated by the reaction is passed into the metal-based film through the one-way tube. After reacting for a certain period of time under high temperature conditions, an azide film can be finally obtained.
[0011] In a preferred technical solution, the polymer material that is easy to spin in step 1 includes polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl butyral, and polyethylene oxide.
[0012] In a preferred technical solution, the metal salt in step 1 includes copper hydroxide, copper acetate, lead acetate, silver oxide, silver nitrate, and cadmium acetate.
[0013] In a preferred technical solution, the concentration of the easily spinnable polymer material in step 1 is 3%-10%.
[0014] In a preferred technical solution, the mass ratio of the polymer material to the metal salt in step 1 is 1:1, 1:2, 2:1, 1:3, 3:1, 2:3, or 3:2.
[0015] In a preferred technical solution, the reaction temperature in step 1 is 25°C-90°C, and the stirring time is 2h-8h.
[0016] In a preferred technical solution, the negative voltage in step 1 is -2k V, the positive voltage is 8kV-20kV, and the pushing rate is 0.05mm / min-0.2mm / min.
[0017] In a preferred technical solution, the hot pressing temperature in step 2 is 100°C-200°C; and the hot pressing time is 5min-30min.
[0018] In a preferred technical solution, the reaction temperature of the azidation in step three is 100°C-150°C, and the reaction time is 1h-36h.
[0019] The principle of the present invention is that a carbon-based azide film suitable for a MEMS microcharge system and having good sensitivity can be quickly prepared by a simple electrospinning and hot pressing combined technology. Hot pressing technology is used to replace the traditional high-temperature calcination process to convert the film containing metal salts obtained by electrospinning into a carbon-based film. Thanks to the large specific surface area of the carbon skeleton, the metal particles are evenly loaded on the carbon skeleton; and the good thermal and electrical conductivity of the carbon skeleton is conducive to the migration of electrons and the conduction of heat. Through the later in-situ azidation process, a carbon-based azide film with good sensitivity can be prepared, and the film properties are kept good, which is conducive to later processing and molding, and matches the MEMS process.
[0020] The beneficial effects of the present invention are as follows:
[0021] (1) The carbon-based azide film of the present invention is rapidly prepared by electrospinning and hot pressing, which is more efficient than the traditional high-temperature calcination process and can be rapidly prepared at a lower temperature in a short time while maintaining good film properties for subsequent processing. The preparation process is relatively simple and can be mass-produced.
[0022] (2) In the carbon-based azide film described in the present invention, the carbon skeleton obtained by the combined electrospinning and hot pressing technology has a large specific surface area, which can evenly load metal particles and effectively avoid agglomeration; at the same time, thanks to the excellent thermal and electrical conductivity of the carbon skeleton, the prepared azide film has better sensitivity performance.
[0023] (3) The final form of the carbon-based azide film described in the present invention is a thin film, which can be cut and easily processed and shaped, is compatible with MEMS technology, and is suitable for MEMS micro-charging. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The film material is prepared by combining electrospinning and hot pressing technology.
[0025] Figure 2 This is a scanning electron microscope image of the carbon-based film obtained after hot pressing.
[0026] Figure 3 This is a scanning electron microscope image of the azide film after in-situ azidation. DETAILED DESCRIPTION
[0027] The present invention is implemented through the following embodiments, but the conditions and results described in the implementation do not limit the content and rights of the invention.
[0028] Example 1
[0029] Carbon-based copper azide film and preparation method:
[0030] Raw materials: polyvinyl butyral (PVB), copper hydroxide (Cu(OH)2), ethanol, sodium azide (NaN3), stearic acid (CH3(CH2) 16 COOH).
[0031] Main instruments and equipment: electrospinning apparatus, magnetic stirrer, hot press, round-bottom flask, water bath.
[0032] 1g of polyvinyl butyral was placed in 10mL of ethanol and stirred at room temperature for 2h, then 1g of copper hydroxide was weighed and added to the PVB solution and continued to stir for 4h, and the stirred solution was injected into a 5mL syringe, and a 20G nozzle (inner diameter of the nozzle was 0.62mm, outer diameter of the nozzle was 0.90mm) was used, and electrospinning was performed at -2kV, 10kV voltage, and a push column rate of 0.1mm / min, and the spun film was placed in a 50℃ oven for drying for 12h. The obtained film was placed in a polytetrafluoroethylene mold, and its surface was evenly wrapped with aluminum foil. A hot press was used to quickly hot press it at 100℃ for 10min to obtain a carbon-based film containing copper hydroxide. Finally, the carbon-based film was placed in the hydrazine gas generated by the reaction of sodium azide and stearic acid, and reacted at 120℃ for 12h to finally obtain a carbon-based copper azide film material.
[0033] Example 2
[0034] Carbon-based lead azide film and preparation method:
[0035] Raw materials: polyvinyl alcohol (PVA), lead acetate ((CH3COO)2Pb), ethanol, sodium azide (NaN3), stearic acid (CH3(CH2) 16 COOH).
[0036] Main instruments and equipment: electrospinning apparatus, magnetic stirrer, hot press, round-bottom flask, water bath.
[0037] Place 1g of polyvinyl alcohol in 10mL of deionized water and stir at 90℃ for 6h, then weigh 1g of lead acetate and add it to the PVA solution and continue stirring for 4h, and inject the stirred solution into a 5mL syringe, use a 20G nozzle, electrospin at -2kV, 10kV voltage, and a push column rate of 0.1mm / min, and place the spun film in a 50℃ oven to dry for 12h. The obtained film is placed in a polytetrafluoroethylene mold, and its surface is evenly wrapped with aluminum foil. A hot press is used to quickly heat press it at 200℃ for 10min to obtain a lead-containing carbon-based film. Finally, the carbon-based film is placed in the hydrazoic acid gas generated by the reaction of sodium azide and stearic acid, and reacted at 120℃ for 12h to finally obtain a carbon-based lead azide film material.
[0038] Example 3
[0039] Carbon-based silver azide film and preparation method:
[0040] Raw materials: polyvinyl alcohol (PVA), silver oxide (Ag2O), ethanol, sodium azide (NaN3), deionized water, stearic acid (CH3(CH2) 16 COOH).
[0041] Main instruments and equipment: electrospinning apparatus, magnetic stirrer, hot press, round-bottom flask, water bath.
[0042] Place 1g of polyvinyl alcohol in 10mL of deionized water and stir at 90℃ for 6h, then weigh 1g of silver oxide and add it to the PVA solution and continue stirring for 6h, and inject the stirred solution into a 5mL syringe, use a 20G nozzle, and perform electrospinning at -2kV, 10kV voltage, and a push column rate of 0.1mm / min, and place the spun film in a 50℃ oven to dry for 12h. The obtained film is placed in a polytetrafluoroethylene mold, and its surface is evenly wrapped with aluminum foil. A hot press is used to quickly heat press it at 100℃ for 10min to obtain a carbon-based film containing silver oxide. Finally, the carbon-based film is placed in the hydrazoic acid gas generated by the reaction of sodium azide and stearic acid, and reacted at 120℃ for 12h to finally obtain a carbon-based silver azide film material.
[0043] Example 4
[0044] Carbon-based cadmium azide film and preparation method:
[0045] Raw materials: polyvinylpyrrolidone (PVP), cadmium acetate ((CH3COO)2Cd), ethanol, sodium azide (NaN3), stearic acid (CH3(CH2) 16 COOH).
[0046] Main instruments and equipment: electrospinning apparatus, magnetic stirrer, hot press, round-bottom flask, water bath.
[0047] 1g of polyvinyl pyrrolidone was placed in 10mL of ethanol and stirred at 50℃ for 4h, then 1g of cadmium acetate was weighed and added to the PVP solution and continued to stir for 4h, and the stirred solution was injected into a 5mL syringe, and a 20G nozzle was used to electrospin at -2kV, 10kV voltage, and a push column rate of 0.1mm / min, and the spun film was placed in a 50℃ oven for drying for 12h. The obtained film was placed in a polytetrafluoroethylene mold, and its surface was evenly wrapped with aluminum foil. A hot press was used to quickly hot press it at 200℃ for 10min to obtain a carbon-based film containing cadmium. Finally, the carbon-based film was placed in the hydrazoic acid gas generated by the reaction of sodium azide and stearic acid, and reacted at 120℃ for 12h to finally obtain a carbon-based cadmium azide film material.
[0048] Example 5
[0049] Carbon-based copper azide film and preparation method:
[0050] Raw materials: polyvinyl butyral (PVB), copper acetate [Cu(CH3COO)2·H2O], ethanol, sodium azide (NaN3), stearic acid (CH3(CH2) 16 COOH).
[0051] Main instruments and equipment: electrospinning apparatus, magnetic stirrer, hot press, round-bottom flask, water bath.
[0052] 1g of polyvinyl butyral was placed in 10mL of ethanol and stirred at room temperature for 2h, then 2g of copper acetate was weighed and added to the PVB solution and continued to stir for 4h, and the stirred solution was injected into a 5mL syringe, and a 22G nozzle (inner diameter of the nozzle was 0.41mm, outer diameter of the nozzle was 0.71mm) was used, and electrospinning was performed at -2kV, 10kV voltage, and a push column rate of 0.2mm / min, and the spun film was placed in a 50℃ oven for drying for 12h. The obtained film was placed in a polytetrafluoroethylene mold, and its surface was evenly wrapped with aluminum foil. A hot press was used to quickly hot press it at 200℃ for 30min to obtain a copper-containing carbon-based film. Finally, the carbon-based film was placed in the hydrazoic acid gas generated by the reaction of sodium azide and stearic acid, and reacted at 120℃ for 12h to finally obtain a carbon-based copper azide film material.
[0053] Example 6
[0054] Carbon-based lead azide film and preparation method:
[0055] Raw materials: polyethylene oxide (PS), lead acetate ((CH3COO)2Pb), ethanol, sodium azide (NaN3), stearic acid (CH3(CH2) 16 COOH).
[0056] Main instruments and equipment: electrospinning apparatus, magnetic stirrer, hot press, round-bottom flask, water bath.
[0057] Place 1g of polyethylene oxide in 10mL of deionized water and stir at 90℃ for 6h, then weigh 2g of lead acetate and add it to the PS solution and continue stirring for 4h, and inject the stirred solution into a 5mL syringe, use a 22G nozzle, electrospin at -2kV, 10kV voltage, and a push column rate of 0.2mm / min, and place the spun film in a 50℃ oven to dry for 12h. The obtained film is placed in a polytetrafluoroethylene mold, and its surface is evenly wrapped with aluminum foil. A hot press is used to quickly hot press it at 200℃ for 30min to obtain a lead-containing carbon-based film. Finally, the carbon-based film is placed in the hydrazoic acid gas generated by the reaction of sodium azide and stearic acid, and reacted at 120℃ for 12h to finally obtain a carbon-based lead azide film material.
[0058] Example 7
[0059] Carbon-based silver azide film and preparation method:
[0060] Raw materials: polyethylene oxide (PS), silver nitrate (AgNO3), ethanol, sodium hydroxide (NaOH), sodium azide (NaN3), stearic acid (CH3(CH2) 16 COOH).
[0061] Main instruments and equipment: electrospinning apparatus, magnetic stirrer, hot press, round-bottom flask, water bath.
[0062] 0.5g of polyethylene oxide was placed in 10mL of deionized water and stirred at 90℃ for 6h, then 1g of silver nitrate was weighed and added to the PS solution and continued to stir for 4h, and the stirred solution was injected into a 5mL syringe, and a 22G nozzle was used to electrospin at -2kV, 10kV voltage, and a push column rate of 0.2mm / min, and the spun film was placed in a 50℃ oven for drying for 12h. The obtained film was placed in a polytetrafluoroethylene mold, and its surface was evenly wrapped with aluminum foil. A hot press was used to quickly hot press it at 200℃ for 30min to obtain a carbon-based film containing silver nitrate, and it was immersed in a NaOH solution and allowed to stand for 30min before being taken out and dried. Finally, the dried carbon-based film was placed in the hydrazoic acid gas generated by the reaction of sodium azide and stearic acid, and reacted at 120℃ for 12h to finally obtain a carbon-based silver azide film material.
[0063] Example 8
[0064] Carbon-based cadmium azide film and preparation method:
[0065] Raw materials: polyvinyl alcohol (PVA), cadmium acetate ((CH3COO)2Cd), ethanol, sodium azide (NaN3), stearic acid (CH3(CH2) 16 COOH).
[0066] Main instruments and equipment: electrospinning apparatus, magnetic stirrer, hot press, round-bottom flask, water bath.
[0067] Place 1g of polyvinyl alcohol in 10mL of deionized water and stir at 90℃ for 4h, then weigh 2g of cadmium acetate and add it to the PVA solution and continue stirring for 4h, and inject the stirred solution into a 5mL syringe, use a 22G nozzle, electrospin at -2kV, 10kV voltage, and a push column rate of 0.2mm / min, and place the spun film in a 50℃ oven to dry for 12h. The obtained film is placed in a polytetrafluoroethylene mold, and its surface is evenly wrapped with aluminum foil. A hot press is used to quickly heat press it at 200℃ for 30min to obtain a carbon-based film containing cadmium. Finally, the carbon-based film is placed in the hydrazoic acid gas generated by the reaction of sodium azide and stearic acid, and reacted at 120℃ for 12h to finally obtain a carbon-based cadmium azide film material.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A carbon-based azide film suitable for MEMS micro-charges, characterized in that: The carbon-based azide film is prepared by using a combination of electrospinning and hot pressing technology and a subsequent in-situ azidation process; specifically, the steps include: Step 1: placing a polymer material that is easy to spin and a metal salt in an organic solvent at a certain mass ratio, stirring evenly, injecting the mixture into a syringe with a nozzle, spinning the mixture using an electrospinning apparatus, and drying the mixture to obtain a film for later use; Step 2: placing the film obtained in step 1 under a hot press for rapid hot pressing at a temperature of 100° C. to 200° C. to obtain a carbon-based film; Step 3: introducing hydrazine gas into the carbon-based film obtained in step 2 to carry out an in-situ azidation reaction, and finally obtaining a carbon-based azide film suitable for MEMS micro-charges; The polymer material in step 1 is polyvinyl butyral.
2. A method for preparing a carbon-based azide film suitable for MEMS micro-charge according to claim 1, characterized in that: The steps include: Step 1: placing a polymer material that is easy to spin and a metal salt in an organic solvent at a certain mass ratio, stirring evenly, injecting the mixture into a syringe with a nozzle, spinning the mixture using an electrospinning apparatus, and drying the mixture to obtain a film for later use; Step 2: placing the film obtained in step 1 under a hot press for rapid hot pressing for 5 min to 30 min to obtain a carbon-based film; Step 3: introducing hydrazine gas into the carbon-based film obtained in step 2 to carry out an in-situ azidation reaction, and finally obtaining a carbon-based azide film suitable for MEMS micro-charges; The polymer material in step 1 is polyvinyl butyral.
3. The preparation method according to claim 2, characterized in that: The metal salt in step 1 includes copper hydroxide, copper acetate, lead acetate, silver oxide, silver nitrate and cadmium acetate.
4. The preparation method according to claim 2, characterized in that: In the step 1, the mass ratio of the polymer material to the metal salt is 1:1, 1:2, 2:1, 1:3, 3:1, 2:3, and 3:2.
Citation Information
Patent Citations
Porous azide / high-energy explosive micro-explosion sequence film and preparation method thereof
CN113307710A
Porous carbon-based nanofiber thin film material loaded by metal monatomic and metal derivative thereof as well as preparation method and application thereof
CN113540478A